2021
DOI: 10.3889/oamjms.2021.6984
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Substance-induced Hippocampal Neurodegeneration in Rodents as Model of Alzheimer’s Dementia

Abstract: BACKGROUND: Alzheimer’s Dementia (AD) cases are increasing with the global elderly population. To study the part of the brain affected by AD, animal models for hippocampal degeneration are still necessary to better understand AD pathogenesis and develop treatment and prevention measures. AIM: This study was a systematic review of toxic substance-induced animal models of AD using the Morris Water Maze method in determining hippocampal-related memory impairment. Our aim was reviewing the methods of AD inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…A systematic review showed that MSG, aluminum chloride, high salt-cholesterol diet caused toxic-substance-induced hippocampal degeneration. Most of those reviewed-studies (52 studies) evaluated neurodegenerative markers including synaptic damage, cytoplasmic swelling, pyknotic nuclei, vacuolization, and hippocampal neuronal shrinkage (27). It also confirmed the presences of apoptosis molecular markers such as Caspase-3, B-cell associated X-protein, B-cell lymphoma protein-2, fluoro jade, and terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL), and neuroglial responses (microtubule associated protein-2, glial fibrillary acidic protein, neuronal nuclei, ionized calcium-binding adaptor molecule-1) (27).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that MSG, aluminum chloride, high salt-cholesterol diet caused toxic-substance-induced hippocampal degeneration. Most of those reviewed-studies (52 studies) evaluated neurodegenerative markers including synaptic damage, cytoplasmic swelling, pyknotic nuclei, vacuolization, and hippocampal neuronal shrinkage (27). It also confirmed the presences of apoptosis molecular markers such as Caspase-3, B-cell associated X-protein, B-cell lymphoma protein-2, fluoro jade, and terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL), and neuroglial responses (microtubule associated protein-2, glial fibrillary acidic protein, neuronal nuclei, ionized calcium-binding adaptor molecule-1) (27).…”
Section: Discussionmentioning
confidence: 99%
“…All rats were sacrificed on day 28 after TMT injection. 15,19 Under ketamine anesthesia (100 mg/kg body weight, intramuscular), transcardial perfusion with phosphate-buffered saline (PBS) was performed. The whole colon was excised, and its length was measured (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Rats in the TMT group were given a single intraperitoneal injection of TMT (8 mg/kg body weight). 15,19 The animals were excluded if they died prematurely. All animal experiments followed a protocol approved by the Ethics Committee of the Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada (reference number: KE/FK/0897/ EC/2019).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation